THE IMPORTANCE OF GEOLOGICAL AND HYDROGEOLOGICAL KNOWLEDGE IN JUSTIFYING PORE PRESSURE PREDICTION: THE CASE STUDY OF THE PECIKO FIELD, LOWER KUTAI BASIN - Agus M Ramdhan (Testing Center for Oil and Gas LEMIGAS, 2017)
One significant factor affecting pore pressure prediction is choosing a method of calculation. If we choose the inappropriate method, the result may not refl ect not only pore pressure condition in an area, but also geological processes operating in the whole basin. In this research, two methods are applied to wireline-based pore pressure calculation in the Peciko Field: the Eaton Method and the Soil Mechanics Method. The results of the calculation show a signifi cant difference between these methods. The Eaton Method resulted in reservoir-shale pressure discrepancy (by over-predicting the reservoir pressure) at shallower depth, and reservoir-shale pressure equilibrium at depth. On the contrary, the Soil Mechanics Method resulted in reservoir-shale pressure equilibrium at shallower depth and an under-predicting at depth. It seems that, in terms of processes operating in this fi eld which affect pore pressure regimes, i.e. lateral reservoir drainage and rapid mud-dominated deltaic sedimentation, the result of the Eaton Method is more plausible than that of the Soil Mechanics Method. This research also reveals an important inference: if there is a pressure discrepancy, then it is likely that a hydrodynamic condition is present.